Aberrant expression of proatherogenic cytokines and growth factors in human umbilical vein endothelial cells from newborns of type 2 diabetic women. (June 2021) - Sultan, Samar
Objectives: This study reports the levels of cytokines, chemokines, and growth factors previously identified as taking part in the pathology of atherosclerosis in human umbilical vein endothelial cells derived from mothers with type 2 diabetes and compares them with those in human umbilical vein endothelial cells derived from healthy mothers under normal glucose conditions. Methods: Cytokine analysis measures of human umbilical vein endothelial cell lysates were obtained using a multiple analyte profiling (xMAP) assay based on magnetic bead-based technology, using the MAGPIX instrument. The correlation between cytokines, chemokines, and growth factors was examined statistically in human umbilical vein endothelial cells derived from mothers with type 2 diabetes. Results: This study showed that the expression of proinflammatory cytokine interleukin-1 alpha was significantly greater in human umbilical vein endothelial cells derived from mothers with type 2 diabetes than those derived from healthy mothers. The protein level of granulocyte colony-stimulating factor was higher in human umbilical vein endothelial cells derived from mothers with type 2 diabetes than those derived from healthy mothers. A significant positive correlation was demonstrated between the protein expression of granulocyte colony-stimulating factor and granulocyte-macrophage colony-stimulating factor in human umbilical vein endothelial cells derived from mothers with type 2 diabetes. Conclusion: Diabetes evokes a persistent inflammatory phenotype in human umbilical vein endothelial cells, as indicated by the enhanced production of cytokines and growth factors under normal glucose conditions.